2020
DOI: 10.1089/neu.2019.6399
|View full text |Cite
|
Sign up to set email alerts
|

Early Osmotherapy in Severe Traumatic Brain Injury: An International Multicenter Study

Abstract: The optimal osmotic agent to treat intracranial hypertension in patients with severe traumatic brain injury (TBI) remains uncertain. We aimed to test whether the choice of mannitol or hypertonic saline (HTS) as early (first 96 h) osmotherapy in these patients might be associated with a difference in mortality. We retrospectively analyzed data from 2015 from 14 tertiary intensive care units (ICUs) in Australia, UK, and Europe treating severe TBI patients with intracranial pressure (ICP) monitoring and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 15 publications
(19 reference statements)
1
5
2
Order By: Relevance
“…Our analysis was different and focused on clinical outcomes, as a result of preference for one of the HOAs and likewise seems to underpin current practices and guidelines. Contrary to our ndings, Anstey et al [27] found that patients who received mannitol compared to patients who received HTS had a higher Marshall CT score (4 versus 3), a higher ISS (42 versus 32) and had a higher predicted probability of 6month mortality using the extended IMPACT score (35% versus 25%) [27]. We did not nd such differences between the group of patients who received mannitol or HTS supporting random variability.…”
Section: Discussioncontrasting
confidence: 89%
“…Our analysis was different and focused on clinical outcomes, as a result of preference for one of the HOAs and likewise seems to underpin current practices and guidelines. Contrary to our ndings, Anstey et al [27] found that patients who received mannitol compared to patients who received HTS had a higher Marshall CT score (4 versus 3), a higher ISS (42 versus 32) and had a higher predicted probability of 6month mortality using the extended IMPACT score (35% versus 25%) [27]. We did not nd such differences between the group of patients who received mannitol or HTS supporting random variability.…”
Section: Discussioncontrasting
confidence: 89%
“…Our participants represent a broad spectrum of patients with serious TBI; demographics, mechanisms of injury, and injury characteristics were similar to those of other international cohorts. [23][24][25] Among those patients matching DECRA eligibility (in whom DC may increase survival with severe disability), we observed infrequent use of secondary DC, in keeping with contemporary evidence and guidelines. However, most patients in our study had injury characteristics that would have excluded them from both DECRA and RESCUEicp.…”
Section: Relationship To Previous Studiessupporting
confidence: 82%
“…We retrospectively collected data on previously managed patients in 14 Intensive Care Units (ICUs) treating TBI patients. The description of data collection has been described previously [10].…”
Section: Study Populationmentioning
confidence: 99%
“…We collected six-hourly serum sodium concentrations from ICU admission until 7 days, or death, whichever came first. We collected data on important aspects of TBI care including neurosurgery (clot evacuation, extra-ventricular drainage, decompressive craniectomy) as well as the use of osmotherapy [10], barbiturate coma and hypothermia (less than 35°C) and daily total desmopressin administered. Finally, we collected outcome data including ICU and hospital mortality, and ICU and hospital length of stay.…”
Section: Data Collectionmentioning
confidence: 99%